THE MODEL OF PENAL MEDIATION AS A COUNTERMEASURES OF VIOLENCE CONFLICT (CAROK) IN MADURESE SOCIETY BASED ON THE LOCAL WISDOM - Cahyono, Cahyono (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2019)
This research is to explore criminal mediation based on local wisdom in dealing with carok violent conflicts in Madurese society. There are two important problems in this study, which is the reason why the criminal justice system is less than optimal in dealing with carok in Madurese society and how criminal mediation can be a model in dealing with conflict based on local wisdom. The research method used in this study is the doctrinal and non-doctrinal methods. By using Freidman's theory and Sociological Jurisprudence related to comparative law, it was found that the criminal justice system is not fully optimal in dealing with carok violent conflicts in Madurese society because of differences in interpreting the concept of justice in the perspective of local communities, the dominance of legalistic perspectives on law enforcement officers and the strong practicality of maintaining self-esteem and religion. The criminal mediation model used by law enforcement officers on Madurese people is based on local wisdom which is a model of family criminal mediation (victim-perpetrators, families, reparations) that is connected to the criminal court system ranging from investigations, closing speeches, examination of cases involving parties warring parties, with mediators, scholars, and law enforcement officials, and the results are written as an act of peace that can be used by the perpetrators to change the sentence. The study recommends that it is very important for law enforcement officials and social leaders, religious scholars and district governments to act as neutral mediators by empowering customary peace institutions that are connected to the criminal justice system.